Commentary on Privacy and confidentiality of patient information: challenges for nursing [original article by Milholland DK appears in J NURS ADM 1994;24(2):19-24]. - Fosbinder D (AONE's Leadership Prospectives)
Topic: An ethical framework that provides nurses with a structure for discussion as they approach issues of patient confidentiality: Purpose: To discuss the use of ownership of and access to information, ethical codes and education for nonprofessionals, information that places patients at risk, dangers and benefits of automated records, universal patient identifiers, and ethics committees to help nurses ensure privacy of the patient's healthcare information. Source: American Nurses Association Code for Nurses. Conclusions: The RN who understands how to protect the confidentiality of the patient's healthcare information will be a true advocate for the patient. People who have access to patient information must be bound by a code of ethics, receive training regarding privacy and state and federal limitations on the transmission of confidential information. [Original article accession number: 1994183277]